Pemberdayaan Jemaat dalam Perspektif Diakonia Transformatif: Studi Implementasi Dana Sharing GPM - Welhelmus Abraham Beresaby (Program Pascasarjana UKIM, 2021)
This article analyses the concept of empowering congregations (oikonomia) as the new concept of the Protestant Church of Maluku (GPM) to add explaining the classic mark of the church, namely fellowship (Koinonia), service (Diakonia), and witness (Martyria). In the provision of services by GPM, the task of empowerment (oikonomia) gets the primary focus. The social context of the GPM congregation living in poverty is the driving force for the mission of church empowerment services. The empowering mission is mainly rooted in the mission of God, who sent the church to realize the kingdom of God to the world. GPM continues the idea of God's mission in service policies by implementing 30% and 70% sharing funds, which focuses on increasing the empowerment of the people as a form of transformative Diakonia. This research used a mixed-method to analyze the implementation of the GPM budget quantitatively, and its utilization was analyzed qualitatively. The congregation of Haria was one of the congregations that became the locus of the research. In the end, the research results that although GPM has mandated the implementation of empowerment programs as the focus of transformative diakonia, the reality is that the church service still prioritizes strengthening institutions and servants.